Modeling emergency department using a hybrid simulation approach - Ahmad, Norazura; Abdul Ghani, Noraida; Kamil, Anton Abdulbasah; Mat Tahar, Razman (Springer Netherlands, 2013)
Within hospital, emergency department is one of the most important unit that involves complex patient movement flow and detailed operational activities. As an integrated system, the efficiency of emergency department depends on its interaction between inter-departmental units and intra-departmental elements.Over the years, with the rapid development of computer technology, there has been a rising trend of using simulation modeling to improve healthcare operations. Discrete-event simulation (DES) has become a popular and effective decision-making tool for modeling the stochastic operational activities in a system. However for a whole system approach, system dynamics (SD) has advantages over DES. SD does not require vast data and is able to capture the inter dependency relations between different units in an integrated system. Both approaches have strengths and weaknesses that may support and complement each other. An integrated model of both approaches will provide a realistic view of a complex system. This chapter provides an overview of the hybrid simulation modeling applications to emergency department.